Perjanjian Pengikat Jual Beli (PPJB) Rumah Pada Pengembang Perumahan Ditinjau Dari Pasal 18 Ayat (1) dan (2) Undang-Undang No. 8 Tahun 1999 Tentang Perlindungan Konsumen - Elisabeth Sesaria Ilka Oktalila; Celina Tri Siwi K.; Diah Imaningrum (Comprehensive Law Journal, 2024)
In buying and selling, Pelita Kebonsari developers as Pelita Kebonsari housing developers make preliminary agreements to bind consumers to the next transaction process. The Sales and Purchase Agreement (PPJB) is a agreement issued by a housing developer to bind consumers who will buy a house. The agreement is made not in front of the notary and made by the housing developer itself. This agreements are usually a standard contracts provided by the developer. It can be used by developers to suppress consumers and attract as much as possible from consumers, although actually the law no. 8. Year 1999 on Consumer Protection has prevented it. The purpose of this research is to know the Sales and Purchase Agreement (PPJB) at the housing developer in terms of Article 18 paragraph (1) and (2) the law no. 8 year 1999 concerning consumer protection to Pelita Kebonsari developer of Malang City and to know responsibility of developer against loss suffered by consumer due to violation of Article 18 of Law no. 8 Year 1999 About Consumer Protection at developer Pelita Kebonsari Malang. The result of the research shows that the implementation of Article 18 paragraph (1) and (2) of Law no. 8 Year 1999 Consumer Protection has been implemented well, but still not fully implemented by Pelita Kebonsari developer. As well as developers Pelita Kebonsari has implemented what is written in Article 19 of Law no.8 of 1999 on Consumer Protection, related to the responsibility of business actors.